Fluoride sources, toxicity and fluorosis management techniques – A brief review - Kashyap, Shreyas J.; Sankannavar, Ravi; Madhu, G.M. (Journal of hazardous materials letters, 2021)
[Display omitted] •Overexposure to fluoride via drinking water causes several health effects including fluorosis.•Endemic fluorosis is still persisted in several countries even with advancement in research.•Most of fluorosis management techniques suggested in the past have come with their own drawbacks.•Defluoridation techniques based on aluminium materials pose serious health risks to the public.•A method which removes excess F−from drinking water without affecting water quality has a scope. Fluoride contamination in drinking water is a global issue. Frequent over-exposure to fluoride causes several health problems such as fluorosis, neurological, thyroid, osteoporosis, etc. The guideline values prescribed by the WHO and other nationals for fluoride in drinking water are reasonable but mostly relevant to fluorosis. However, these guideline values cannot be satisfied in some regions due to economic and financial shortcomings. Several fluorosis management techniques were suggested to address excess fluoride in drinking water, but each have specific drawbacks. Defluoridation techniques like the Nalgonda technique, reverse osmosis (RO), and adsorption using activated alumina have found to be promising to reduce fluoride concentration within the prescribed limits, and RO water is most widely used for drinking in fluorosis affected regions. However, these techniques are still associated with certain drawbacks, and prior research on this theme has focused on one dimension of removing excess fluoride from water. Hence, it is essential to understand the basic problems associated with fluoride contamination, such as sources of fluoride exposure, adverse health effects and defluoridation techniques feasibility. Furthermore, perception of the effect of co-existing ions with fluoride in drinking water is crucial in deciding fluoride toxicity level and developing efficient strategies for fluorosis mitigation.